Carbohydrate-Mimetic Peptides for Pan Anti-Tumor Responses - Kieber-Emmons, Thomas; Saha, Somdutta; Pashov, Anastas; Monzavi-Karbassi, Behjatolah; Murali, Ramachandran (Frontiers in Immunology, 2014)
Molecular mimicry is fundamental to biology which transcends to many disciplines ranging from immune pathology to drug design. Structural characterization of molecular partners has provided insight into the origins and relative importance of complementarity in mimicry. Chemical complementarity is easy to understand; amino acid sequence similarity between peptides, for example, can lead to cross-reactivity triggering similar reactivity from their cognate receptors. However, conformational complementarity is difficult to decipher. Molecular mimicry of carbohydrates by peptides is often considered one of those. Extensive studies of innate and adaptive immune responses suggests the existence of carbohydrate mimicry, but the structural basis for this mimicry yields confounding details; peptides mimicking carbohydrates in some cases fail to exhibit both chemical and conformational mimicry. Deconvolution of these two types of complementarity in mimicry and its relationship to biological function can nevertheless lead to new therapeutics. Here, we discuss our experience in bringing a tumor-associated carbohydrate mimetic peptide to the clinic. Emphasis is placed on the rationale, the lessons learned from the methodologies to identify mimics, a perspective on the limitations of structural analysis, the biological consequences of mimicking tumor associated carbohydrate antigens and the notion of reverse engineering to develop carbohydrate mimetic peptides in vaccine design strategies to induce responses to pan-glycan antigens expressed on cancer cells.